“MENJADI PENYIAR CILIK” (KEGIATAN PEMBERDAYAAN BAGI SISWA SEKOLAH RAKYAT ANCOL 2) - Girsang, Lasmery Rosentauly Maissalinya (Universitas Bunda Mulia, 2019)
In general, broadcasting is a part of communication skill that can be gained through commercial agents/workshop or at university. Besides that, directly practice of broadcasting is still rare announced to public. Based on that situation and condition, Communication Department from Bunda Mulia University tries to share the knowledge of broadcasting through empowerment activity to school that applies broadcasting as the major. In this case, the school needs to implementation in studio room but has not provided by facility yet. Therefore, this empowerment activity runs by giving not only oral material, but also the practice of equipments inside TV studio. In brief, the results of this activity can introduce and enable the students of Sekolah Rakyat Ancol 2 (located in North Jakarta) to actualize their roles as news presenter, camera person, switcher, floor director as a whole unity in a broadcasting process. PKM activities are implemented by combining lecture techniques (giving material) and direct practice. During the initial 60 minutes, students are provided with material related to script writing and broadcasting techniques. In order not to appear stiff, the lecture delivered was supported by the seating arrangement of U shape so that participants surrounded the speakers. Then afterwards, for approximately 2 hours, participants practiced individually and in teams. The results of this study in general explain curiosity indeed strongly encourages participants to practice. It is hoped that in the future, PKM activities will be long-term through training / similar programs with more varied topics / themes. Keywords: broadcasting, empowerment, student, folk school